Delay-optimal spectrum decision method for cognitive network - Wu-jian SUN; Na LI; Yang LIU; Le SUN; Tao CHEN; Hao LI; Ou LI (Tongxin xuebao)
Spectrum decision was investigated within the confine of spectrum management framework for cognitive radio networks.Sensing errors in PHY layer,outage probability on wireless channel and multiple interruptions of primary user were taken into consideration.Probability-based and sensing-based spectrum decision methods were proposed,which were capable of balancing traffic evenly among licensed.For the probability-based method,short-time first discipline was employed to further shorten average residual time,closed-formed expression were presented based on dynamical programing.For the sensing based method,new channel could be chosen for uncompleted transmission,which alleviated the time spent in waiting primary user.Optimal residual time was obtained by choosing the minimal value of the two methods.Furthermore,spectrum heterogeneity was taken into consideration and theoretical analysis was of general sense.Simulation results validate the approach is efficient.